2004
DOI: 10.1353/rhe.2004.0032
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries and Quandaries: How Professors Negotiate Market Relations

Abstract: Closer university-market relations are evidenced in increased university patenting, the formation of start-up companies, and partnerships with industry. They are part of a state and policy effort to link science and engineering to the market, thereby developing new technologies, stimulating economic growth, and creating new jobs. Yet the blurring of boundaries between the two institutions creates quandaries for faculty and administrators. Using a National Science Foundation database and interviews, this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…This tendency has been facilitated by graduate students' valuable research skills for the new demands of the global market, and, as a consequence, industry representatives have supported graduate students through assistantships (Slaughter et al, 2002). However, in a more recent study, Slaughter, Archerd, and Campbell (2004) found that professors understood that graduate students were cheap labor but valued them primarily as apprentices and future colleagues. Other arguments found in the literature against graduate training through industry partnerships include the type of values indirectly transmitted through applied projects.…”
mentioning
confidence: 99%
“…This tendency has been facilitated by graduate students' valuable research skills for the new demands of the global market, and, as a consequence, industry representatives have supported graduate students through assistantships (Slaughter et al, 2002). However, in a more recent study, Slaughter, Archerd, and Campbell (2004) found that professors understood that graduate students were cheap labor but valued them primarily as apprentices and future colleagues. Other arguments found in the literature against graduate training through industry partnerships include the type of values indirectly transmitted through applied projects.…”
mentioning
confidence: 99%
“…Others have disagreed, arguing that these trends distract faculty from its mission to further basic knowledge (e.g. Cohen et al 1998;Campbell and Slaughter 1999;Slaughter, Archerd, and Campbell 2004). Others have adopted intermediate positions by saying that industry-academia associations are complementary to basic research and a combination of both provides better training to students (e.g.…”
Section: Industry-academia Collaborations: a Literature With Mixed Mementioning
confidence: 99%
“…Thus, the possibility of faculty to profit through public-subsidised resources by patenting and commercialising products derived from their research seems to be against faculty contribution to the public good (e.g. Slaughter and Leslie 1997;Campbell and Slaughter 1999;Krimsky 2003;Slaughter, Archerd, and Campbell 2004;Gumport 2005;Mendoza and Berger 2005;Owen-Smith 2005). Conversely, others argue that the commercialisation of faculty research actually serves better the public good because it allows the transfer of technology to industry more efficiently.…”
Section: Industry-academia Collaborations: a Literature With Mixed Mementioning
confidence: 99%
See 1 more Smart Citation
“…with external entities are struggling to meet promotion and tenure requirements and the demands of their external partners (Boardman and Ponomariov 2007;Few et al 2007;Slaughter et al 2004), it is important that higher education institutions address these complications so as not to undermine faculty work or hinder social and technological progress.…”
mentioning
confidence: 99%